Collective behavior in Iraqi society (36 AH.656 m ....... 132 AH 750 m) (Journal of the College of Basic Education, 2019)
The collective behavior of the Iraqi society has been exposed to what can be called the conspiracy. The Umayyad treated the society with caution and hatred at the same time, resulting in the attachment of some of the charges for the purpose of its political and social settlement. It represents the opposition to Umayyad authority and the environment that is the incubator of the opposition movements. The revolution of Imam Hussein bin Ali (peace be upon him) and up to the revolution of Zaid bin Ali through the movements of Musab bin Zubayr and Mokhtar al-Thaqafi and the revolution of Abdul Rahman bin al-Ash'ath and others, all of which was the Iraqi environment is incubator. The Umayyads tried to attribute this to Imam Ali Ibn Abi Talib (peace be upon him), and everyone knows the value and importance of Imam Ali being One of the great men of Islam and this statement wanted the Umayyads to convey the message that the people of Iraq are the people of division and hypocrisy and speech to Imam Ali bin Abi Talib, and this means that the speech carries credibility and accuracy, a lot, if not all credibility at all, History and stand on the above statement, and who said it، And it turned out that the saying is the brainchild of the governor, Hajjaj bin Yusuf al-Thaqafi and the governor of Iraq appointed by the Umayyad caliph Abdul Malik bin Marwan after the first managed to control the rebellion of Abdullah ibn al-Zubayr in Mecca in 73 AH, Vkavah and eye on Iraq, With the Iraqis in the way he sees fit, and so began his first engagement with the Iraqis, and he takes up his new political position, addressing the Iraqis in Kufa, saying (O people of Iraq, the people of division, hypocrisy and the disadvantages of ethics) and thus became the above statement resonant and influential added the Umayyad another taste when they attributed later Imam Ali bin Abi Tal (Peace be upon him) to resonate among the people in general to reduce the Iraqi opposition to the Umayyads, and the reasons are always political